Preparation, characterization, and electrical conductivity investigation of multi-walled carbon nanotube-filled composite nanofibres - Abdul Hamid, Nurfaizey; Salim, Mohd Azli; Md. Saad, Adzni; Mohd Rosli, Mohd Afzanizam; Abdul Munajat, Nurain; Esa, Siti Rahmah; Tucker, Nick (Universiti Malaysia Perlis, 2021)
There is a growing interest in carbon nanofibre materials especially for applications that require high surface area, excellent chemical inertness, and good electrical conductivity. However, in certain applications a much higher electric conductivity is required before one can take the full advantage of the nanofibre network. Therefore, incorporating superconductive materials such carbon nanotubes is thought to be a feasible approach to enhance the electrical properties of the carbon nanofibres. The objectives of this study were to prepare and characterize multi-walled carbon nanotube-filled composite nanofibres. Carbon nanofibres were produced via electrospinning technique using precursor solutions of polyacrylonitrile in dimethylformamide loaded with different amount of multi-walled carbon nanotubes (MWCNT). The electrospun fibre samples were then pyrolyzed in a nitrogen-filled laboratory tube furnace. Characterization process was performed using scanning electron microscope (SEM), transmission electron microscope (TEM), and four-point probe method. It was found that the incorporation of MWCNT into the carbon nanofibre structures could significantly increase the electric properties of the nanofibres. The composite nanofibres with 0.1 wt.% of MWCNT loading has the highest electrical conductivity of 155.90 S/cm compared to just 10.71 S/cm of the pure carbon nanofibres. However, the electrical conductivity of the composite fibres reduced drastically when higher weight percentages of MWCNT were used. This was caused by agglomeration of MWCNT causing premature percolation, and broken fibre network as evidenced by SEM and TEM examinations. The results obtained from this study may facilitate improvements in the development of superconductive high surface area materials for electronic applications.